2014
DOI: 10.1002/ams2.39
|View full text |Cite
|
Sign up to set email alerts
|

Importance of smoking and the occurrence of acute poisoning due to waterproof spray

Abstract: A search of the database Ichushi (Japana Centra Revuo Medicana), which collects summaries of Japanese medical articles, was undertaken to identify articles published between 1983 and 2013, using the key word "waterproof". There was one original article and 19 case reports describing acute poisoning due to inhalation of waterproof spray gas, and providing information about the patient's smoking habit. Twenty-three of the 25 cases (92% of male patients, 71% of female patients) had a smoking habit. The one female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The study identified some characteristics of WAP and compared them to those of AEP and summer-type HP. As in previous reports, patients with WAP had common clinical characteristics, such as dyspnea, cough, and fever, [ 5 ] a history of smoking, [ 1 ] and bilateral ground-glass opacities on CT scans. [ 1 ] The features characteristic of WAP were rapid disease progression and macrophage dominance in the BALF.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The study identified some characteristics of WAP and compared them to those of AEP and summer-type HP. As in previous reports, patients with WAP had common clinical characteristics, such as dyspnea, cough, and fever, [ 5 ] a history of smoking, [ 1 ] and bilateral ground-glass opacities on CT scans. [ 1 ] The features characteristic of WAP were rapid disease progression and macrophage dominance in the BALF.…”
Section: Discussionmentioning
confidence: 70%
“…The inhalation of waterproofing spray containing fluororesin causes acute poisoning and lung injury, [ 1 3 ] which is referred to as waterproofing spray-associated pneumonitis (WAP) in this report. The Japan Poison Information Center reported that WAP occurs in approximately 68 people per year in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhalation of waterproofing spray containing fluororesin causes acute poisoning and lung injury [1][2][3], which is referred to as waterproofing spray-associated pneumonitis (WAP) in this report. The Japan Poison Information Center reported that WAP occurs in approximately 68 people per year in Japan [4].…”
Section: Introductionmentioning
confidence: 99%
“…That study reported that 93% of the affected males and 71% of the females had a smoking habit and that the white blood cell count (WBC) and C-reactive protein (CRP) level were related to the inhaled maximum concentration of the waterproofing spray to which the subjects had been exposed [3]. A review of twenty-five cases indicated that WAP is associated with tobacco smoke exposure, including secondhand smoke, and is characterized by lung edema on computed tomography (CT) scans [1]. However, those reports did not describe the detailed laboratory, radiographic, or histopathologic findings.…”
Section: Introductionmentioning
confidence: 99%